IMPLEMENTASI MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE GIVING QUESTION AND GETTING ANSWER DALAM MENGEMBANGKAN KEAKTIFAN DAN KREATIVITAS BELAJAR SISWA PADA MATA PELAJARAN PAI - Arifah, Siti Aisyatul; Ummah, Kholifatul; Putriani, Putriani (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
Abstract The teacher's role in learning is not just the transfer of knowledge to students, but as a motivation and mediator who guides and conditions students to learn, so that they can acquire knowledge and skills and independently develop the knowledge they have learned. This process can be achieved by implementing a learning process that requires students to be more active in exploring, solving problems and learning in small groups, namely by implementing the Cooperative Learning model of giving questions and getting answers. This research aims first, to understand how to apply the giving question and getting answer type cooperative learning model in PAI learning. Second, to understand the implications of the cooperative learning model of giving questions and getting answers on students' cognitive and affective abilities. This research method applies a descriptive qualitative approach. The type of research used is a case study. The form of research used is field research. The techniques used in collecting this data were free interviews, participatory observation, and documentation with PAI teachers and 10th grade students at Miftahul Ulum Bondowoso High School. The results of this research show that students responded positively to the giving question and getting answer learning method. This learning method utilizes simple learning media, and has better results when used at the final stage of learning, in order to determine students' mastery of understanding of the Islamic religious education learning material that has been presented previously. The giving question and getting answer method allows students to receive direct feedback regarding their progress in class and their appreciation for the assignments completed.